Empirical analysis of path effects on prediction equations of pseudo-velocity response spectra in northern Japan. - Dhakal, Yadab P.
We study path effects on prediction equations of pseudo velocity response sheets (natural period of 0.1-5.0s) in northern Japan, where heterogeneous attenuation structure exists. The path effects have been examined by comparing the regression analysis results for two different prediction equations. The first equation consists of a single term of anelastic attenuation conventionally. The second equation consists of two terms of anelastic attenuation in consideration of the heterogeneous attenuation structure. In the second equation, we divide a source to site distance into two distances at the attenuation boundary beneath the volcanic front. The boundary is considered to separate the relatively high Q fore-arc side mantle wedge (FAMW) from the low Q back arc side mantle wedge (BAMW). Strong motion records (hypocentral distances less than 300 km) from interplate and intraslab events with Mw 5.1-7.3 are used. Regression analysis shows that the standard errors are significantly reduced by the second prediction equation at short periods (0.1-0.5s), whereas the difference in standard errors from both prediction equations is negligible at intermediate and long periods. The Qs values (quality factor for S-wave) converted from two anelastic attenuation coefficients for the second prediction equation are remarkably similar to the path-averaged Qs values for the FAMW and BAMW by other studies using spectral inversion method. From these findings, we conclude that the path effects on the prediction equation of pseudo-velocity response spectra are satisfactorily accomplished by the second prediction equation.
Keywords: Path effect; Volcanic front; Q value; Anelastic attenuation; Response spectra